Congenital disorders of glycosylation - Mendes, Ana Raquel (2022)
Congenital disorders of glycosylation are a highly variable, rapidly expanding family of genetic diseases that result from defects in the synthesis of glycans. The vast majority of these monogenic diseases are inherited in an autosomal recessive way, but some types follow an autosomal dominant or X-linked inheritance. The present work aimed to review the state of the art of congenital disorders of glycosylation, including available therapeutic options, and present a simplified diagnostic approach to this group of diseases. Congenital disorders of glycosylation can be classified into four categories: N-linked glycosylation defects, O-linked glycosylation defects, combined glycosylation defects, and glycosphingolipid and glycosylphosphatidylinositol anchor synthesis defects. The phenotype may range from mild to severe, depending on disease severity. Clinical features include dysmorphic features, neurologic, dermatologic, cardiac, endocrine, immunologic, hematologic, gastrointestinal and liver involvement, and skeletal muscle abnormalities. As there is no universal or pathognomonic sign or symptom and no sensitive diagnostic test, it is of foremost importance to keep a high index of suspicion of these diseases. When a congenital disorder of glycosylation is suspected, the first step in screening is to perform serum transferrin isoelectric focusing. Molecular genetic testing is the most specific diagnostic test. Treatment is usually symptomatic, with specific treatment only available for some of these disorders. Since congenital defects of glycosylation may affect any organ at any age and have variable clinical presentation, they should be considered in the differential diagnosis of any patient with multiorgan involvement.